A National Study of the Use of Asymptomatic Systemic Imaging for Surveillance Following Breast Cancer Treatment - Schumacher, Jessica R. (Ann Surg Oncol, 2018)
BACKGROUND: Though not guideline recommended, studies suggest 50% of locoregional breast cancer patients undergo systemic imaging during follow-up, prompting its inclusion as a Choosing Wisely measure of potential overuse. Most studies rely on administrative data that cannot delineate scan intent (prompted by signs/symptoms versus asymptomatic surveillance). This is a critical gap, as intent is the only way to distinguish overuse from appropriate care. Our objective was to assess surveillance systemic imaging post-breast cancer treatment in a national sample accounting for scan intent. METHODS: A stage-stratified random sample of 10 women with stage II-III breast cancer in 2006–2007 was selected from each of 1,217 Commission on Cancer accredited facilities for a total of 10,838 patients. Registrars abstracted scan type (CT, non-breast MRI, bone scan, PET/CT) and intent (cancer-related versus not, asymptomatic surveillance versus not) from medical records for 5 years post-diagnosis. Data was merged with each patient’s corresponding National Cancer Database record, containing sociodemographic and tumor/treatment information. RESULTS: Of 10,838 women, 30% had ≥1 and 12% had ≥2 systemic surveillance scans during a four-year follow-up period. Patients were more likely to receive surveillance imaging in the first follow-up year (lower proportions during subsequent years), and if they had ER/PR negative tumors. CONCLUSIONS: Locoregional breast cancer patients undergo asymptomatic systemic imaging during follow-up despite guidelines recommending against it, but at lower rates than previously reported. Providers appear to use factors that confer increased recurrence risk to tailor decisions about systemic surveillance imaging, perhaps reflecting limitations of data on which current guidelines are based.